Diagnostic performance of three non-invasive fibrosis scores (Hepamet, FIB-4, NAFLD fibrosis score) in NAFLD patients from a mixed Latin American population - Zambrano-Huailla, Rommel (2020)
Introduction and aims Several non-invasive scoring systems have been developed and validated worldwide to predict the risk of liver fibrosis in nonalcoholic fatty liver disease (NAFLD). However, information about the performance of these systems in Latin American populations is scarce. Our aim was to evaluate the performance of the Hepamet Fibrosis Score, Fibrosis-4 (FIB-4) and the NAFLD Fibrosis Score (NFS) in a mixed Latin American group of NAFLD patients. Methods Clinical, laboratory and liver biopsy data collected from 379 biopsy-proven NAFLD patients from Latin American tertiary health centers were reviewed. Histological fibrosis stages were classified using the Kleiner score. Accuracy was determined, and new fibrosis score thresholds were calculated to better compare the performances of non-invasive tests and to explore their usefulness in excluding fibrosis. Results The distribution of fibrosis stages among the sample population was as follows: F0 (45%), F1 (27%), F2 (8%), F3 (16%) and F4 (4%). Using modified thresholds, the areas under the ROC curves (AUROC) for Hepamet and FIB-4 (0.73 and 0.74, respectively) to detect significant fibrosis were higher than that of NFS (0.58). However, the AUROCs of the three scores were not significantly different in advanced fibrosis and cirrhosis. To exclude fibrosis, we calculated lower cutoffs than standard thresholds for Hepamet, FIB-4 and NFS with similar performances. Conclusion Thresholds of non-invasive fibrosis scores (Hepamet, FIB-4 and NFS) can be modified to maximize diagnostic accuracy in Latin American patients with NAFLD.